2015
DOI: 10.3109/03014460.2015.1020873
|View full text |Cite
|
Sign up to set email alerts
|

Wealth, health and frailty in industrial-era London

Abstract: These results might indicate strong selective mortality operating during childhood or the effects of migration in the industrial-era population of London.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 97 publications
2
41
0
Order By: Relevance
“…What is anomalous to this situation, however, is the higher frailty scores in the presumably elite monastically-associated females than the lower status nonmonastic females. Although physiological stress does not always correlate with SES groups [65, 66], this anomaly is explained likely by the few females in this sample (N total = 23), and their unequal age distribution, within and outside the monastic setting. The contribution of age disparities to female frailty underscores this effect.…”
Section: Discussionmentioning
confidence: 98%
“…What is anomalous to this situation, however, is the higher frailty scores in the presumably elite monastically-associated females than the lower status nonmonastic females. Although physiological stress does not always correlate with SES groups [65, 66], this anomaly is explained likely by the few females in this sample (N total = 23), and their unequal age distribution, within and outside the monastic setting. The contribution of age disparities to female frailty underscores this effect.…”
Section: Discussionmentioning
confidence: 98%
“…Expectation of life at age twenty, however, was in the range of 39–43 years (Hollingsworth, ), regardless of socioeconomic status (Razzell and Spence, ; Razzell and Spence, ). DeWitte et al () found a lack of compelling differences in mortality between high‐and low‐status adults, but elevated mortality and reduced survival among low‐status juveniles in a skeletal sample from industrializing London. This could be because the social gradients in selective mortality noted in modern populations had not yet surfaced, or perhaps surfaced first in juveniles (Razzell and Spence, ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be because the social gradients in selective mortality noted in modern populations had not yet surfaced, or perhaps surfaced first in juveniles (Razzell and Spence, ). If selection disproportionately targeted low‐socioeconomic children, as suggested by DeWitte et al (), stature in the adult population would be less heterogeneous, as only the hardiest of the low‐status population would survive into adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations